ANATOMICAL DISSECTION AS A LEARNING TOOL: AN EXPERIENCE REPORT (REMUNOM, 2025)
This experience report stems from the teaching project entitled "Unraveling Anatomy in Practice: Dissection as a Teaching Tool and Production of Didactic Resources." The activity was organized and carried out by the League of Applied Morphofunctional Sciences of Faculty of Medicine of Mucuri, at the Federal University of Vales Jequitinhonha and Mucuri, with the aim of providing participating students with the experience of human dissection, enhancing anatomical structure visualization, developing practical skills, and producing additional cadaveric anatomical parts for other medical students at the institution. The objective of this report is to present and discuss the impact of the teaching project on the participating students' learning in the field of human anatomy. The impact was assessed through perception questionnaires administered to the project members after the practice period, which included questions related to anatomical learning, organizational aspects, technical development, and ethical reflection. The results indicated strong student engagement, with students reporting that the experience broadened their perspective on visualizing the abdominal viscera and peritoneum more clearly, as well as the opportunity to develop new skills and foster greater ethical reflection on the use of cadavers for teaching. Therefore, we conclude that despite some challenges encountered throughout the project, such as uncertainty in performing the procedures and balancing the availability of students, technicians, and faculty, the project achieved its objectives in terms of teaching and producing teaching materials, while also reinforcing the importance of dissection practice in medical training.